The memory-work sessions: Exploring critical pedagogy in tourism. (November 2017) - Rouzrokh, Mahsa; Muldoon, Meghan; Torabian, Pooneh; Mair, Heather
Abstract: The paper reports on a pedagogical 'experiment' undertaken by scholars aiming to critically reflect on tourism and tourism studies. Memory-work, a feminist, qualitative methodology, was chosen because it centres critical tourism inquiry within the context of sharing meaningful, personal experiences. The team met regularly to engage in supportive, critical dialogue about their memories and to spark critical reflections about tourism more broadly. Four substantive themes (embodied remembering, gendered bodies, racialized bodies, and embodying the gaze) were developed from collective analyses of initial discussions. A deeper reflection on the potential of this approach for engendering critical tourism pedagogy was also undertaken to explore its potential as critical tourism pedagogy. Five pedagogical themes (building safe spaces and developing trust, creating empathy, engaging tourism literature in 'real life', opening doors for ongoing reflection, and decentring power and knowledge) were identified. The paper concludes with recommendations for adapting this approach to their own tourism teaching and learning endeavours.